The chair and the valley : a memoir of trauma, healing, and the outdoors - Lyon, Banning (The Open Field/Penguin Life, Viking, an imprint of Penguin Random House LLC, 2024)
"An incredible memoir about one man's journey to heal from his trauma through chosen family, friendship, and nature. Banning Lyon was your average 15-year-old, living in Dallas, TX. He enjoyed listening to punk rock music, skateboarding, and even had a part-time job. But in January 1987 his life quickly changed after a school guidance counselor falsely believed he was suicidal after giving away a skateboard. A few days later, he was admitted into a hospital and what he was told would be a two-week stay turned into 353 days that would change his life forever. Banning takes readers through his fraught relationship with his family, the abuse he suffered at the hospital, the lawsuit against the owners of the hospital that would make him a millionaire, and his desire to try and make sense of what happened to him. We witness Banning navigate the difficult landscape of trauma and his daily battle to live a normal life. After years of highs and lows that include being adopted by his lawyer and mentor, falling in love and grieving the death of his fiancé, and being sued by the same doctors who abused him, Banning decides to take control of his life and finds hope in the terrains of Yosemite National Park, where he discovers his purpose for being a backpacking guide. Through therapy, friendship, and nature, Banning finds the strength to keep moving forward. The Chair and The Valley is a raw, gut-wrenching, and incredible story about healing from your trauma and starting over. It is a testament to the power of chosen family, the restorative power of nature, and the strength it takes to show up for yourself every day"--